Infectious Mononucleosis and Multiple Sclerosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
A cohort of 25,234 Danish patients testing positive (at titers of 1/32) for Epstein-Barr virus related mononucleosis (MONO), during the period 1940-1988, was followed for more than 550,000 person-years.